Perancangan Sistem Pendukung Keputusan Pemilihan Laptop Terbaik Berbasis WEB Menggunakan Metode Simple Additive Weighting - Muhammad Iqbal Yasin; Furqan Khalidy; Saiful Amir (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Selecting the right laptop is a challenge for consumers due to the wide variety of brands, specifications, and prices available on the market, including for customers of B-Computer, a technology device store located in Binjai City. This difficulty arises because choosing a laptop requires considering multiple criteria simultaneously, such as price, processor, RAM, storage, VGA, weight, and battery life, while consumers' limited technical knowledge often makes the decision-making process complicated and time-consuming. This study aims to design and implement a web-based Decision Support System (DSS) to help consumers determine the best laptop according to their needs and budget in an objective and measurable way. The method used in this study is Research and Development (R&D), applying the Simple Additive Weighting (SAW) method, a weighted sum method that normalizes the decision matrix based on benefit and cost criteria to produce a ranking of laptop alternatives. The system was built using the JavaScript programming language and a MySQL database. Black Box Testing results show that all system features, including admin login, laptop data management, criteria preference input, and the calculation and display of recommendation results, function properly, achieving a 100% success rate across all tested scenarios. The application of the SAW method in this system is proven capable of producing objective, accurate, and scientifically accountable laptop recommendations, thereby simplifying and speeding up the consumer decision-making process without the need to manually compare laptop specifications.